Dam on John Englishs Gully - Branch Cultural Historical Association (2010)
John Englishs Gully was dammed in 1949 to provide the first municipal water supply. Marina Gambin writes her fathers response to her inquiry on Englishs identity, A fellow by the name of John English used to go out there in the summertime and strip off and jump into it to wash himself. This would have been long before 1949. Gullies are also favoured places for wildlife such as foxes, mink and weasels. Other gullies in and around Branch include Muskrat Gully, Otter Gully, Mount Gully, Tom Dunns Gully and Slatey Gully a favourite place for children to find writing slates in the early days when school paper was in short supply.